Teachers’ self-assessment of their teaching effectiveness at higher secondary level in Pakistan: a case study - Quddus, Lubna; Khalid, Mukhdoom; Muhammad Waris, Ali Khan (KnE Social Sciences, 2019)
Self-assessment is a process of continuous reflection, self-monitoring, and selfjudgment, to review an individual’s strengths and weaknesses and helps to discover areas which need improvement. It involves an individual’s learning from his experiences, by judging his personal, educational as well as his professional performance. Selfassessment enables teachers to get control over their progress. It can serve as one of the most influential tools for the measurement of teacher quality. The researcher of this study administered a questionnaire which consisted of two parts. Part one comprised of SITE II (Self-assessment Instrument for Teacher Evaluation II) on which teachers rated themselves, and part two was designed to explore teachers’ opinion about the effectiveness of self-assessment. The sample comprised of 107 teachers of higher secondary level. The basic motive of the researcher was to enhance learning through self-assessment to know if such self-assessment exercises may promote quality teaching in classrooms. It was found that the respondents viewed that self-assessment helps them understand their strengths and weaknesses. It establishes teachers’ involvement in self-learning, which can serve as a sound basis in the teaching process. By doing self-assessment, teachers can re-consider as to how they are teaching in their classrooms.